AB0782 EXPLORING OCCURRENCE AND CORRELATES OF SLEEP DISTURBANCES AND FATIGUE IN PSORIATIC ARTHRITIS PATIENTS. (13th June 2020) - Haugeberg, G.; Hoff, M.; Michelsen, B.; Kavanaugh, A.
Abstract : Background: Psoriatic arthritis (PsA) patients have been reported to suffer from increased sleep disturbances (1) and fatigue (2). Sleep disturbances and fatigue in PsA may not only be influenced by skin and musculoskeletal manifestations, but also by psychosocial consequences of the disease and the patients' mental status (3). Objectives: To explore the occurrence and correlates of sleep disturbances and fatigue in PsA clinic patients. Methods: A broad data collection was completed from 137 PsA patients including demographics, disease activity measures for both skin and musculoskeletal involvement and patient reported outcome measures. Pain was reported on a VAS scale 0-100 mm and sleep and fatigue on a numeric rating scale (NRS) 0-10. Depression was scored as: 1 not, 2 moderately and 3 extremely depressed. Sleep disturbances and fatigue were defined as present if the NRS score was ≥5. Descriptive statistics (mean (SD) for continuous variables and percentage for categorical variables) were applied. Associations were explored using univariate and adjusted linear regression analyses, with inclusion of variables in multivariate analysis that had a p value <0.2 in univariate analyses. Results: Demographic patient characteristics: mean age 52.3 (SD 10.3) years, BMI 28.4 (4.3) kg/m2, women 50.4%, current smoker 17.5%, living together 76.6%, working 54.8%. Musculoskeletal disease status: PsA disease duration mean 8.8 (SD 6.8) years, CRP 5.0 (8.3) mg/L, 68 tender joint count (68TJC) 10.1 (11.1), 66 swollen joint count 0.6 (1.0), MASES enthesitis score 3.0 (3.2). Psoriasis skin status: PASI 2.6 (3.7) and itching skin 23.1%. Patient reported outcome measures: pain 34.8 (23.3) mm, sleep disturbances 3.5 (2.9), fatigue 4.2 (2.6), MHAQ 0.44 (0.40) and depression 1.4 (0.4). Mean numbers of comorbidities was 0.72 (0.93) and 45.3% exercised ≥1 time per week and 32.4% currently used bDMARDs and 58.4% csDMARDs. The prevalence of sleep disturbances was 38.0% and that of fatigue 44.5%. Identified associations with impaired sleep disturbances in univariate analyses were female gender, higher BMI, smoking, not working, higher scores for 68TJC, MASES score, pain, fatigue, depression, lower MHAQ, not exercising and itching skin. For fatigue the identified associations were female gender, smoking, not working, higher scores for 68TJC, MASES score, pain, sleep disturbances, depression, lower MHAQ and itching skin. In adjusted analysis only pain, fatigue and higher MHAQ were independently associated with sleep disturbances and pain, sleep disturbances and depression were independently associated with fatigue. Conclusion: The prevalence of sleep disturbances and fatigue was frequently reported in our PsA patients. No measures reflecting skin involvement or objective measures of inflammatory musculoskeletal involvement were independently associated with sleep disturbances and fatigue. Our data suggest that patient's perceptions of musculoskeletal involvement (pain or MHAQ) play an important role causing sleep disturbances and fatigue in PsA patients. However, mental status also seems to play an important role in the perception of fatigue. References: [1]Duvetorp A, et al. Arch Dermatol Res 2019;311:351-60. [2]Husted JA, et al. Ann Rheum Dis 2009;68:1553-8. [3]Husni ME, et al. Semin Arthritis Rheum 2017;47:351-60 Disclosure of Interests: Glenn Haugeberg: None declared, Mari Hoff: None declared, Brigitte Michelsen Grant/research support from: Research support from Novartis, Consultant of: Consulting fees Novartis, Arthur Kavanaugh Grant/research support from: Abbott, Amgen, AstraZeneca, BMS, Celgene Corporation, Centocor-Janssen, Pfizer, Roche, UCB – grant/research support